Spatial conditions for car dependency in mid-sized European city regions. Issue 7 (3rd July 2021) - Wiersma, J. K.; Bertolini, L.; Harms, L.
ABSTRACT: We analysed the spatial conditions for Car Dependency (CD) in three European cities and their suburbs, to investigate the following research question: What are the potential travel mode alternatives to the car, and how do they relate to actual travel behaviour? We defined CD as the lack of alternative transport modes to the car for reaching daily destinations. We selected three mid-sized city regions with different planning traditions and travel behaviour: Eindhoven, Southampton and Aachen. The results demonstrate that the differences in CD in the three cities are not substantial. The suburbs show a substantially higher CD than the city proper; however, when considering the e-bicycle as an alternative transport mode, this difference decreases. Daily amenities are largely within walking distance, in cities as well as in suburbs. For the daily commute there seems to be great potential for the (e)-bicycle as most employees, living both in the cities and their suburbs, currently live within 15 km of their jobs. Overall, our research shows that the differences in the actual modal split in the three cities cannot be explained by differences in the spatial conditions for CD.